Treatments of dentition with four dens evaginatus and reverse overbite: a case report with a 6-year follow-up - Mengyin Luan; Qiang Wang; Yixuan Fang; Xiaoying Wang (BMC Oral Health)
Abstract Background Dens evaginatus is a dental anomaly characterized by a conical cusp or tubercle on the occlusal surface. It is generally believed to be caused by the protrusion of the dental papilla toward the enamel organ during odontogenesis, followed by the formation of enamel, dentin, and dental pulp. Owing to the abrasion of the occlusal surface, the protrusive cusp will be quickly worn off, uncovering the dental pulp tissue and thereby giving rise to pulpal or periapical disorders in the affected tooth. Abnormal occlusion can also exert an impetus in facilitating the wear process of dens evaginatus. Case presentation This article presents a case of a patient possessing dens evaginatus on four first premolars, leading to diverse consequences such as abnormal abrasion, acute apical abscess and periapical cysts. The patient also exhibited reverse overbite on the left side dentition, which potentially accounted for the varying degrees of wear on the dens evaginatus. Regarding teeth with different disorders, we had attained favorable therapeutic outcomes through various approaches including progressive grinding, root canal treatment, and periapical surgery, and had conducted follow-up for 6 years. The results indicated that the treatment effects were stable and the teeth functioned properly. Conclusion This report demonstrates effective therapeutic approaches for the diverse clinical manifestations resulting from dens evaginatus, and suggests that if a tooth was found with dens evaginatus during intraoral examination, other corresponding teeth should also be examined carefully. Occlusion anomalies may exert a promotional effect on the wear of the deformed central cusp.